Randomized Comparison of Isosorbide Mononitrate and PGE2 Gel for Cervical Ripening at Term including High Risk Pregnancy - Agarwal, Kavita; Batra, Achla; Batra, Aruna; Aggarwal, Abha (International Journal of Reproductive Medicine, 2014)
Aims. Prostaglandin E2 is the most commonly used drug for cervical ripening prior to labour induction. However, there are concerns regarding uterine tachysystole and nonreassuring fetal heart (N-RFH). Isosorbide mononitrate (IMN) has been used successfully for cervical ripening. The present study was conducted to compare the two drugs for cervical ripening at term in hospital. Methods. Two hundred women with term pregnancies referred for induction of labour with Bishop score less than 6 were randomly allocated to receive either 40 mg IMN tablet vaginally (n=100) or 0.5 mg PGE2 gel intracervically (n=100). Adverse effects, progress, and outcomes of labour were assessed. Results. PGE2 group had significantly higher postripening mean Bishop score, shorter time from start of medication to vaginal delivery (13.37 ± 10.67 hours versus 30.78 ± 17.29 hours), and shorter labour-delivery interval compared to IMN group (4.53 ± 3.97 hours versus 7.34 ± 5.51 hours). However, PGE2 group also had significantly higher incidence of uterine tachysystole (15%) and N-RFH (11%) compared to none in IMN group, as well as higher caesarean section rate (27% versus 17%). Conclusions. Cervical ripening with IMN was less effective than PGE2 but resulted in fewer adverse effects and was safer especially in high risk pregnancies.